Housing the rural millions - a tough task? - Joshi, Navin Chandra (1996)
A tiny house of one's own is still a distant dream for millions of rural folk in the country, says the author. The struggle for housing is not just a struggle for land but also for control over housing resources, building materials, technology and finance. Underlining the need for developing a viable and self-reliant housing finance facility in the villages, the author calls for popularization of the concept of low cost housing by encouraging the use of substitutes and cheaper building materials. The services of PRIs, NGOs, co-operative societies, private builders and even NRIs should be availed of to mitigate the sufferings of the shelterless villagers, he suggests. - Reproduced
Keywords: Non governmental organizations - India; Panchayat - India; Housing - India; Housing